Do papillomaviruses cause feline cutaneous squamous cell carcinoma? - Teh, Alexander; Krockenberger, Mark (Veterinary Evidence, 2021)
PICO question In cats infected with papillomavirus, is the risk of developing feline cutaneous squamous cell carcinoma greater than cats that are not infected with papillomavirus? Clinical bottom line Category of research question Risk The number and type of study designs reviewed Eleven papers were critically reviewed, nine were case-control studies and two were experimental in vitro studies Strength of evidence Moderate Outcomes reported Infection of feline epithelial skin cells with Felis catus papillomavirus type 2 (FcaPV-2) is a risk factor for the development of feline cutaneous squamous cell carcinoma. The pathogenesis of FcaPV-2 infection and neoplastic transformation into malignant cells shares similar pathways to the human papillomavirus (HPV) model of pathogenesis and carcinogenesis with some differences Conclusion In conclusion, there is moderate strength of evidence in the literature to support a role of FcaPV-2 in the development of cutaneous squamous cell carcinomas in cats. Therefore, prevention of infection with FcaPV-2 should prevent some cancers How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.